2010
DOI: 10.1590/s1519-69842010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Urinary parameters of Trichechus inunguis (Mammalia, Sirenia): reference values for the Amazonian Manatee

Abstract: The Amazonian manatee, Trichechus inunguis (Natterer 1883) is endemic to the Amazon Basin and is currently considered a vulnerable species. In order to establish normality ranges of urinary parameters to help monitor the health of this species in captivity, chemical urinalyses were performed on twelve males and nine females of various age groups. Urine was collected once a month for twelve months in the tanks just after being drained, by placing stainless steel containers under the genital slit of females and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
10
0
4
Order By: Relevance
“…In our previous research (Pantoja et al, 2010), we measured quantitative levels of glucose by a chemical analyzer, and found no statistically significant difference between sexes and age classes, leading to the establishment of a normal range (3.0 to 3.6 mg/dL) for this parameter.…”
Section: Glucosementioning
confidence: 86%
See 1 more Smart Citation
“…In our previous research (Pantoja et al, 2010), we measured quantitative levels of glucose by a chemical analyzer, and found no statistically significant difference between sexes and age classes, leading to the establishment of a normal range (3.0 to 3.6 mg/dL) for this parameter.…”
Section: Glucosementioning
confidence: 86%
“…The only available information on the urine of this species derives from analyses conducted in the Laboratory of Aquatic Mammals (LMA) of the Instituto Nacional de Pesquisas da Amazônia (INPA), Manaus, Amazon, Brazil. Some of these results were recently published (Pantoja et al, 2010), using urinalysis in order to establish normal ranges of urinary parameters to help monitor the health of this species in captivity. To accomplish this, the authors performed chemical urinalysis to obtain quantitative values of glucose, urea, creatinine, uric acid and amylase levels obtained using colorimetric spectrophotometry.…”
mentioning
confidence: 99%
“…Buscando estudos sobre o desmame de mamíferos em cativeiro, são mais observados análises com espécies domésticas, dentre os quais se observa o desmame de leitões onde houve a variação no comportamento e nas características do sistema digestório. (ARAÚJO et al, 2011;ROBLES-HUAYNATE et al, 2013). Estudo do comportamento animal são importantes no campo científico e se mostram relevantes para conservação de espécies ameaçadas de extinção como embasamento para reintrodução de animais e para promover o bem-estar animal (SNOWDON, 1999).…”
Section: Introductionunclassified
“…O peixe-boi-da-amazônia é um animal herbívoro, que na natureza se alimenta especialmente de plantas emergentes, representadas principalmente por gramíneas (COLARES & COLARES, 2002). Quando em cativeiro, os filhotes são alimentados com fórmulas artificiais fornecidas por meio de mamadeiras ou com plantas dos gêneros Urochloa, Halodule, Gracilaria, Cryptonema, dentre outros, além de frutos, legumes e verduras (COLARES et al, 2000;PANTOJA et al, 2010;ANZOLIN et al, 2014;BARBOSA et al, 2013). No presente trabalho, três espécies de plantas foram ofertadas: Pistia stratiotes L., conhecida como "alface d'água"; Eichornia crassipes (Mart.)…”
Section: Introductionunclassified
“…Robin rigged up a canvas sling with a hole in the bottom, in which a manatee could be suspended over a graduated cylinder to collect urine for analysis (Figure 7). Unfortunately, Robin never lived to publish the results; however, they were dug from the project's files and used in a paper as recently as 2010 (Pantoja et al, 2010).…”
mentioning
confidence: 99%